Syriac hagiography: texts and beyond - Minov, Sergey; Ruani, Flavia (Texts and studies in Eastern Christianity, 2021)
Introduction / Sergey Minov and Flavia Ruani -- Part I. Texts as Literature: 1. Prologues as Narthexes in Syriac Hagiographies / Jeanne-Nicole Mellon Saint-Laurent -- 2. Hearing Sanctity: Oral Performance and Aural Consumption of Hagiographical Stories in the Late Antique and Medieval Syriac Milieu / Reyhan Durmaz -- 3. Objects as Narrative Devices in Syriac Hagiography / Flavia Ruani -- Part II. Saints Textualized: 4. Pope Sylvester: How to Create a Saint: The Syriac Contribution to the Sylvestrian Hagiography / Annunziata Di Rienzo -- 5. The Syriac Martyrdom of the Mimes and the Performance of Biblical Recitation: Questions of Power and Contexts / Cornelia Horn -- 6. The Syriac Life of Mār Yāret the Alexandrian: Promoting the Cult of a Monastic Holy Man in Early Medieval Mesopotamia / Sergey Minov -- 7. Prose, Poetry, and Hagiography: The Martyrdoms of Jacob the Persian and Tahmizgard in Syriac Story and Song / Adam Carter Bremer-McCollum -- 8. The Memory of the Persian Martyrs in St Nikodemos' Synaxaristes (1819) / Sebastian P. Brock -- Part III. Beyond the Texts: 9. Between Gift and Commodity: The Distribution of Tokens and Material Substances at the Pilgrimage Sites of Stylites / Dina Boero -- 10. St Stephen in Amida in a New mimro of Jacob of Serugh: Christianity vs Zoroastrianism in a Clash of Religious Shrines / Muriel Debié -- Index.